Methodological Choice and Design
XII, 311 p.
Keywords: Beginning and well-seasoned researchers alike face major challenges in understanding the complexities of research designs arising from within and across methodological paradigms as well as in applying them in ways that maximize impact on knowledge, practice and policy. This volume offers crucial reinterpretations of established research methodologies in light of contemporary conditions. It also presents a critical introduction to some contemporary research approaches yet to gain general recognition. It charts and analyzes the conceptual and practical complexities of a variety of research designs for contemporary educational and social work research, providing readers what they need not only to design technically sound and coherent research studies but also to develop methodologically innovative research projects that cross the boundaries between different methodological traditions to the benefit of scholarship, policy, and practice.